Mediating effect of symptom severity on the relationship between aggression, impulsivity and quality of life outcomes among patients with schizophrenia and related psychoses - Sagayadevan, Vathsala; Satghare, Pratika; Jeyagurunathan, Anitha; Koh, Yen Sin; Shafie, Saleha; Chang, Sherilyn; Samari, Ellaisha; Subramaniam, Mythily (Frontiers in Psychiatry, 2023)
Aims: Aggression and impulsivity among individuals with schizophrenia have been associated with poor clinical outcomes including worsening of symptoms and substance abuse which have been linked to a lower quality of life (QoL). The current study aimed to look at the mediating effect of symptom severity on the relationship between aggression, impulsivity and QoL among outpatients with schizophrenia and related psychoses in a multi-ethnic Asian population. Methods: Data (n=397) were collected from outpatients seeking treatment at the Institute of Mental Health. The World Health Organization Quality of Life-BREF (WHOQOL-BREF) scale, the Symptoms Checklist-90 Revised (SCL-90-R), Buss Perry Aggression Questionnaire (BPAQ), and the Barratt Impulsiveness Scales (BIS) were used to assess subjective well-being, symptom severity, aggression, and impulsivity respectively. Mediation analysis was performed using the PROCESS macro to understand the mediating effect of symptom severity. Results: Motor impulsivity (MI) was indirectly associated with both the physical and psychological health domains of QoL while self-control was indirectly associated with the physical, psychological, and environmental health QoL domains through increased symptom severity. Conclusions: The significant indirect effect of symptom severity in our study highlights one potential pathway through which impulsivity impacts the QoL of individuals with schizophrenia and related psychoses. Elucidating other factors besides symptom severity that have an indirect effect on the QoL of individuals provides alternative approaches for treatment through which better clinical outcomes can be achieved.